Mathematische Lernvideos zu Studieneinstieg und Studienvorbereitung - Liebendörfer, Michael; Biehler, Rolf; Schmitz, Angelika

Tailoring Code Property Graphs to Jimple - Youkeim, Michael Hany Fawzy
The increased complexity of modern software has led to much more sophisticated attack vectors. As a result, we require newer vulnerability detection methods to ensure software security without compromising efficiency. The Code Property Graph (CPG) is a program representation that provides a comprehensive overview of program behavior, combining abstract syntax trees, control flow graphs, and program dependence graphs. With such a detailed data structure, we can detect patterns that characterize known vulnerabilities and identify various security threats. Querying the combined data structure instead of the individual graphs enables the detection of multidimensional scenarios. This work aims to integrate the advantages of CPGs into software systems that utilize the Jimple intermediate representation. We introduce JimNode, a novel approach for generating CPGs specifically tailored to Jimple. Despite the model incompatibility, our evaluation, which covered approximately 50,800 methods, reveals an 88.07% similarity of the inter-statement edges compared to Joern, the state-of-the-art tool for CPG generation. We provide a detailed analysis of our methodology and discuss why it is better suited for Jimple programs than Joern’s language-agnostic approach.

Music and Religions in the 21st Century – Introduction - Höink, Dominik; Meyer, Andreas (Music and Religions in the 21st Century)

Knowledge Management in Civil Protection at the Example of Fire Brigades - Schultz, Andreas Maximilian; Dotzki, Fabian; Mozgova, Iryna (Proceedings of the 16th International Joint Conference on Knowledge Discovery, Knowledge Engineering and Knowledge Management)
Knowledge management is essential for successful disaster management. This paper conducts a Systematic Literature Review at the intersection of the knowledge management field and disaster management and examines the available body of literature. Fire departments are chosen as the focus group as they are the most prevalent emergency services. There are many publications that deal with knowledge management during the response phase of an emergency. Often, the literature focuses on the application of knowledge management in large-scale disasters to link the various organizations on-scene. What is missing in most approaches is a prior step of implementing and training the knowledge management system. Therefore, this literature review seeks to provide an overview of approaches for daily routines and small-to-medium incidents that serve as a training ground. However, literature on non-incident phases and smaller incidents is scarce. As information technologies are developing rapidly, there is no modern and recent description of the current use of knowledge management solutions in this area.
Keywords: Knowledge Management; Civil Protection; Systematic Literature Review; Fire Brigade

Interventionskonzepte zur Förderung von motorischen Basiskompetenzen - Niederkofler, Benjamin; Strotmeyer, Anne; Kehne, Miriam (Motorische Basiskompetenzen. Konstrukt, Erfassung und Anwendung)

Duale Karrieren: Chronischer Stress und protektive Ressourcen - Längsschnittstudien im Vergleich zweier Verbundsysteme - Breithecker, Jennifer; Kehne, Miriam (Sport, Bewegung und Gesundheit in internationaler Perspektive. Festschrift zur Verabschiedung von Prof. Dr. Hans Peter Brandl-Bredenbeck)

Moment or movement – the heterogeneous impact of the Black Lives Matter movement on personal and societal charitable crowdfunding campaigns - Seutter, Janina; Müller, Michelle; Müller, Stefanie Jutta Marianne; Kundisch, Dennis (Internet Research)

"Die Geschichte als Dichterin". Analogien in kleinen historischen Porträts von Stefan Zweig. - Öhlschläger, Claudia (Lektüren der Ähnlichkeit um 1900. Modi der Sinnerzeugung in der klassischen Moderne.)

Sonderpädagogischer Förderbedarf: Grundschule zwischen Inklusion und Selektion. - Kottmann, Brigitte (Handbuch Grundschulpädagogik und Grundschuldidaktik.)

An approach to use generic data sets for neural networks in product designs through geometric abstraction via primitives - Ott, Manuel; Meihöfener, Niclas; Mozgova, Iryna (Proceedings of the 11. Conference on Mass Customization and Personalization (MCP))
Generative design suggestions and topology optimizations can help to reduce iterative process loops between calculation and design departments during product development processes. However, precise topology optimizations are computationally intensive, while generative designs benefit from swift suggestions to address design problems efficiently. Using artificial neural networks (ANN) can address this contrast of pre-defined aims by predicting topology-optimized designs, thereby combining both advantageous features. However, a challenge in Mass Customization is, that ANN are usually trained on specific geometries, making transfer to other applications impractical or requiring the creation of new datasets, which is economically unfeasible. Authors have already demonstrated a solution in other publications: dividing a geometry into geometric primitives like cuboids to perform abstraction. An ANN can then be trained to recognize optimized cuboids, which can be assembled back into a complete geometry, comparable to the finite element methods, which divide geometries of parts in finite elements enable mechanical property calculation. This publication aims to illustrate the steps of the approach in which the complete geometry of a part is segmented into these primitives, and the benefits obtained. Various methods will be explored, including automated workflows on modern low-code platforms, to enable generalized use.

State of Knowledge Management among German firefighters - Schultz, Andreas Maximilian; Dotzki, Fabian; Mozgova, Iryna (Proceedings of the 21st ISCRAM Conference)

Enabling Performance Portability for Shallow Water Equations on CPUs, GPUs, and FPGAs with SYCL - Büttner, Markus; Alt, Christoph; Kenter, Tobias; Köstler, Harald; Plessl, Christian; Aizinger, Vadym (Proceedings of the Platform for Advanced Scientific Computing Conference (PASC))

Der Medienbegriff als Element einer Strukturlogik professionalisierten Handelns von Medienpädagog*innen. Eine biografische Perspektive. - Dehmel, Lukas (merzWissenschaft)

Multimodal Communicative Behaviours in Shy Children in Assessment Situations and Social Evaluative Contexts - Viertel, Franziska E.; Tolksdorf, Nils Frederik (Contemporary Issues in Early Childhood Education and Care)
Shy children are characterised by reserved communicative behaviour, especially in novel situations or when interacting with unfamiliar interlocutors. Many of the contextual elicitors that trigger typical patterns of shyness reactions in children, such as gaze aversion, a more distant approach, or general hesitation, may be present in typical laboratory settings or in standardised testing situations, for example, language assessment tests. In our chapter, we review recent studies that operationalise shy children’s communicative behaviour at verbal and nonverbal levels with different social partners, such as humans or social robots, as interaction partners, providing practitioners with a sound overview of communicative signals that are challenging to capture and measure in practical settings. From this, we derive critical implications for the design of testing situations for children that allow them to unfold their communicative potential and demonstrate their linguistic competence, taking into account their individual temperamental characteristics.

Preschoolers' Interactions with Social Robots: Investigating the Potential for Eliciting Metatalk and Critical Technological Thinking - Tolksdorf, Nils Frederik; Wildt, Eugenia; Rohlfing, Katharina (Companion of the 2024 ACM/IEEE International Conference on Human-Robot Interaction)

Language Learning with Media and Technology in (Early) Childhood - Rohlfing, Katharina; Wildt, Eugenia; Tolksdorf, Nils Frederik (Dzieciństwo. Literatura i Kultura)
Nowadays, from early on, children are exposed to technology and media, and six-month-olds are even expected to use some. There is a wide range of products for babies and toddlers. This article reviews the current state of the art, examining the robustness of word knowledge learned using technologies such as e-books, computer games, digital pens, and social robots, and how individual differences among children impact language learning with technology. It aligns with interactive learning theories, positing that learners need to engage in an interaction in order to construct new knowledge.

Concert à Stuttgart? Réflexions sur le rapport entre l’opéra comique de Scribe et d’Auber et la cour de Wurtemberg - Münzmay, Andreas (Auber et Scribe, un patrimoine lyrique vivant. Le Concert à la cour (1824). Actéon (1836))

Experimentally Verified 22 kW, 40 kHz LLC Resonant Converter Design with new Control for a 1 MW Cascaded H-Bridge Converter - Unruh, Roland; Böcker, Joachim; Schafmeister, Frank (ECCE Europe 2024; IEEE Energy Conversion Congress & Exposition Europe)
Although there are numerous design and control methodologies for the LLC resonant converter, they often do not consider decentralized control strategies to operate them as isolated DC-DC converters within a cascaded H-bridge. The total output power of all LLC converters must be constant to supply a load such as a wa- ter electrolyzer. However, each individual LLC converter can vary its output power as long as the total output power remains constant. This opens new possibilities in increasing the system efficiency and robustness. Usually, the DC-link voltage of each module capacitor shows a 2nd harmonic voltage ripple. However, the total stored energy in all DC-link capacitors is constant within a grid period for a balanced three-phase system. By controlling each LLC converter’s output power locally to be proportional to the energy stored in its DC-link capacitor, modules with a lower instantaneous DC-link voltage transfer less power to the load than modules with a higher DC-link voltage. As a result, a higher efficiency, voltage gain and lower peak resonant capacitor voltage can be achieved with the same components. The 22.2kW experimental prototype of the LLC converter reaches an efficiency of over 97% at resonance which is similar to the precalculated value.
Keywords: Cascaded H-Bridge; Converter Losses; Decentralized Control; Full-Bridge Converter; LLC Resonant Converter

Aufbruch in Grenzen. Akademisierung und Professionalisierung weiblicher Berufe am Beispiel der Katholischen Fachhochschule Nordrhein-Westfalen 1970–1989 - Priesching, Nicole; Henkelmann, Andreas; Nordblom, Pia; Özdemir, Derya

Context-specific adaptation for head fakes in basketball: a study on player-specific fake-frequency schedules - Güldenpenning, Iris; Böer, Nils Tobias; Kunde, Wilfried; Giesen, Carina G.; Rothermund, Klaus; Weigelt, Matthias (Abstracts of the 66th Conference of Experimental Psychologists)